Trends in patient, surgeon, and procedural characteristics of intraocular lens exchange among Medicare beneficiaries 2011 to 2020 - Huang, Jane; Dun, Chen; Son, Hyeck Soo; Makary, Martin; Daoud, Yassine; Srikumaran, Divya; Chang, David F.; Woreta, Fasika A. (Journal of cataract and refractive surgery, 2025)
Purpose:  - To assess trends in prevalence and patient/surgeon characteristics of intraocular lens (IOL) exchange surgery in the United States and to evaluate the surgical complication rates. - Setting:  - Medicare beneficiaries. - Design:  - Retrospective cross-sectional analysis. - Methods:  - Medicare beneficiaries aged 65 years or older who underwent IOL exchange surgery between 2011 and 2020 were identified from 100% Medicare fee-for-service carrier claims data. Main exclusion criteria: missing demographic information and incomplete follow-up data. Main outcomes: incidence of IOL exchange, patient-level and surgeon-level factors, and postoperative complication rates. - Results:  - 52 583 IOL exchanges were performed on 48 967 patients. The annual number of IOL exchanges increased from 4621 in 2011 to 6114 in 2019. Most patients were White (n = 47 228, 89.8%), resided in urban locations (n = 44 095, 84.0%), and had a Charlson comorbidity index of ≤2 (n = 41 556, 79.0%). Of 7493 surgeons, most were male (n = 6308, 84.2%), practiced in urban locations (n = 6907, 92.2%), and had an average of 24.7 ± 11.2 years between medical school graduation and the last surgery they performed during the study period. The most common surgical indications were mechanical lens failure (n = 22 252, 51.4%) and lens displacement (n = 9155, 21.1%). The most common complications were epiretinal membrane (ERM) (n = 531, 6.8%), mechanical lens complication (n = 460, 5.9%), and dislocation of the replacement IOL (n = 385, 4.9%). - Conclusions:  - The number of IOL exchange procedures performed among Medicare beneficiaries increased over the past decade. Male ophthalmologists in urban locations performed the majority of IOL exchanges. The most common postoperative complication was ERM. The rates of corneal decompensation, retinal detachment, and endophthalmitis were low.
Gesehen am 26.01.2026